The Disclosure of Sustainability Report Based on GRI 300 on Agricultural Companies Listed on The Indonesia Stock Exchange The Year 2020-2022 - Mufida, Farah Ayu; Kurnia Ekasari, Kurnia Ekasari; Wahyuni, Hesti (PT. EQUATOR SINAR AKADEMIA, 2024)
The purpose of the study was to study and compare the level of completeness of disclosure of the Sustainability Report of companies in Sub-Sector of agriculture listed on the Indonesia Stock Exchange. The type of research used is qualitative research with a method of descriptive analysis of secondary data sustainability reports year from each company year 2020 to 2022. In general, the disclosure of environmental topics from seven companies in the agricultural sub-sector listed on the Indonesia Stock Exchange rose in 2021 and 2022 when compared to 2020. This shows that the level of concern for the seven companies to the community and stakeholders increases. The total GRI Standards for general disclosures and specific topics are 32 disclosures. At PT Astra Agro Lestari Tbk, PT Austindo Nusantara Jaya Tbk, PT Eagle High Plantation, and PT Sawit Sumbermas Sarana Tbk there is an increase in disclosure of sustainability reports. On the other hand, at PT Cisadane Sawit Raya Tbk the same every year. While PT Dharma Satya Nusantara Tbk experienced a decline and PT Mahkota Group Tbk had fluctuations. The company with the highest level of completeness is PT Austindo Nusantara Jaya Tbk with an average of 85% which discloses as much and the company with the lowest level of completeness is PT Cisadane Sawit Raya Tbk of 13%.In terms of the efforts of companies in the environmental aspect in general have made the best efforts and comply with government regulations. These companies disclose their commitments, efforts, and achievements in their sustainability reports, even with business targets and prospects.